Correlation Analysis of Parental Knowledge About Acute Respiratory Infection With Toddler Nutritional Status in Coastal Communities: A Review - Nadia Dwihajra Musrin; Sitti Marzuqoh Aidah Basri (Journal of Health Science and Pharmacy, 2025)
Background: Acute Respiratory Infection (ARI) remains a significant public health concern in both developing and developed countries due to its high morbidity and mortality rates. ARI is an infectious disease and the leading cause of death among children under five years old worldwide, with nearly 7 million deaths reported annually. Objective: This study aims to analyze vendor behavior in relation to the presence of lead in fried snacks sold along Mandonga Mall Street. Methods: This study employed secondary data obtained from a literature review using Google Scholar and PubMed, with publication years ranging from 2019 to 2025. Results: The findings indicate that improving parental knowledge and fostering a supportive environment are essential strategies in preventing ARI, thereby reducing morbidity and mortality in toddlers. Conclusion: Parental knowledge regarding ARI plays a crucial role in the early identification of symptoms, provision of appropriate home care, and prevention of complications, all of which contribute to maintaining child health. Nevertheless, improvements in children’s nutritional status are also influenced by multiple factors, including dietary intake, parenting practices, family economic conditions, and access to healthcare services. Keywords: Knowledge, Acute Respiratory Infection, Toddler